Dye-sensitized solar cells using natural dyes extracted from plumeria and celosia cristata flowers / Siti Noraini Abu Bakar … [et al.] - Abu Bakar, Siti Noraini; Abdullah, Huda; Mohamad Mahbor, Kamisah; Kamarullah, Shahida Hanum (Penerbit UiTM (UiTM Press), 2016)
In this study, extracted plumeria and celosia cristata flowers have been used as the sensitizer for dye-sensitized solar cells (DSSC). The cells were fabricated using Ti0₂ as a semiconductor layer deposited on transparent Indium doped tin oxide (ITO) conductive glass using a spin coating technique. The films with dyes were characterized by UV-VIS absorption spectra. The photovoltaic properties of DSSC were studied under an incident irradiation of 100 mW/cm². The I-V characteristic curves of all fabricated cells were measured and analysed. The energy conversion efficiency (ƞ) of the cells consisting of plumeria extract and celosia cristata extract was 3.73 x lO⁻⁶ and 1.18 x10⁻⁷, respectively.